DIAGNOSIS OF FOLLICULAR THYROID TUMORS - N. V. Ivanova; V. G. Polyakov; R. V. Shishkov; А. I. Pavlovskaya; N. А. Koshechkina; Т. Р. Panferova; I. N. Matveeva (Сибирский онкологический журнал)
Diagnostic value of preoperative and intraoperative imaging of follicular thyroid tumors in children was assessed. Between 1982 and 2012, a total of 96 patients aged from 3 to 17 years were treated. There were 30 patients with minimally invasive thyroid cancer and 66 with follicular adenoma. The preoperative imaging methods were found to be capable of suspecting malignancy, however, they were unable to differentiate benign from malignant tumors. Minimally invasive follicular cancer was diagnosed in 76,7 % of patients using the findings of ultrasound tomography, in 66,6 % by fine-needle biopsy and in 60 % of cases by urgent histological test. Urgent histological test for patients with follicular thyroid lesions is justified in cases with preoperative cytological diagnosis of follicular thyroid tumor and suspicion of cancer. Results of urgent histological test confirmed the diagnosis of minimally invasive thyroid cancer in 90 % of patients. Routine histological examination allowing capsular or vascular invasion to be detected is the main morphological diagnostic method for patients with follicular thyroid nodes.